ASSESSMENT OF THE EFFICACY OF CETYLPYRIDINIUM CHLORIDE-CONTAINING DRUGS IN TOPICAL TREATMENT OF ACUTE PHARYNGITIS, LARYNGITIS AND CATARRHAL TONSILLITIS IN CHILDREN - E. A. Lebedinskaya; N. P. Utkina; N. B. Merzlova; O. V. Lebedinskaya (Вопросы современной педиатрии, 2013)
The efficacy and convenience of topical antiseptic drug usage in treatment of acute pharyngitis, laryngitis and catarrhal tonsillitis in children are described in this article.